Blackstone's guide to the UK Internal Market Act 2020 - Bates, Alan; McGurk, Brendan; Peretz, George; Williams, Jack (Barrister) (Oxford : Oxford University Press, 2021)
This work explores the Internal Market Act's provisions, as an Act creating the foundation for freedom of trade within the UK following Brexit.
This edition also issued in print: 2021.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on December 16, 2021).
Keywords: Great Britain; Markets -- Law and legislation -- Great Britain; Commercial law -- Great Britain; Great Britain -- Politics and government -- 2007-